Wewenang Notaris Dalam Pengalihan Perjanjian Lisensi Merek Melalui Jual Beli - Alifia Radhita Widorini; Rahandy Rizki Prananda (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2023)
Marks can be transferred or transferred due to inheritance, will, waqf, grants, agreements, or other reasons justified by laws and regulations. This paper attempts to describe the implementation of the transfer of a brand license agreement through buying and selling and the authority of a notary in transferring a brand license agreement through buying and selling. This study uses a normative juridical research method with a statutory approach. The results of the study show that the transfer of a brand license agreement through buying and selling adheres to the principle of freedom of contract as long as it fulfills the legal terms of the agreement. The role of the notary in transferring the brand license agreement through buying and selling is authorized to make authentic deeds that have perfect evidentiary power and are binding on the parties.